Відділ нових культур: минуле, сучасне та майбутнє - Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The data on the history of New Cultures Department of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are given in the paper. The basic stages of the Department making, development of scientific directions and formation of plant collections are characterized. The modern state of scientific activity, the role of the leading scientists in researches carried out in the Department, the main directions of the work, conditions of the collection plots are shown. The role of New Cultures Depart ment as an important center of introduction and selection of forage, technical, spice and vegetable plants are described.